1976
DOI: 10.1021/bi00650a027
|View full text |Cite
|
Sign up to set email alerts
|

The primary structure of myohemerythrin

Abstract: The complete amino acid sequence of muscle hemerythrin (myohemerythrin) from the sipunculid Themiste (syn. Dendrostomum) pyroides has been determined by analysis of tryptic, chymotryptic, and cyanogen bromide peptides. The primary structure of myohemerythrin differs substantially from that of coelomic hemerythrins of Phascolopsis (syn. Golfingia) gouldii and Themiste pyroides, the amino acid sequence of the muscle protein being only 46 and 45% homologous with the respective coelomic hemerythrins. The most exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The transformation matrix in this program is calculated by the Kabsch (20) algorithm. This superposition shows that previous sequence alignments ( [21][22][23] that placed the deletion between residues 90 and 96 were misaligned by 1 residue. cur as monomers (myohemerythrin), dimers, trimers, tetramers, and octamers.…”
mentioning
confidence: 68%
“…The transformation matrix in this program is calculated by the Kabsch (20) algorithm. This superposition shows that previous sequence alignments ( [21][22][23] that placed the deletion between residues 90 and 96 were misaligned by 1 residue. cur as monomers (myohemerythrin), dimers, trimers, tetramers, and octamers.…”
mentioning
confidence: 68%
“…low methionine and arginine contents (Nejmeddine et al, 1988) and the apparent high resemblance observed previously (Demuynck et al, 1991 j between the N-terminal region of the MP I1 and the myohemerythrin of Themiste zostericola (Klippenstein et al, 1976) misidentified by the authors as Themiste pyroides according to Hendrickson and Ward (1 977). Cyanogen bromide cleavagc of the nativc protein followed by RP-HPLC scparation resulted in the isolation and subsequently sequencing of two fragments, MI and M2 (see Fig.…”
Section: Sequencing Of the Proteolytic Fragments From The Mp I1mentioning
confidence: 85%
“…In fact, among the 119 amino acids of the MP 11, the sequence comparison revealed 97 and 76 identical amino acid positions with Lhe myohcmcrythrin reported in the Fame species N. diversicolor (Takagi and Cox. (Takagi and Cox, 1991) and 7: zostericolu (Klippenstein et al, 1976). 4, 5 and 6. hemerythrins subunits of 7: pyroides (Ferrell and Kitto, 1971).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptide homologs of the MHr C helix (14), and the omission-series peptides used to identify antigenic sites (see below), were made by a method of simultaneous multiple peptide synthesis in which the peptide resins were contained in individual solvent-permeable packets (15). Crude peptides were purified to >90% homogeneity by reverse-phase highperformance liquid chromatography (16).…”
Section: Methodsmentioning
confidence: 99%